Rangeland degradation and recovery in China's pastoral lands - Squires, Victor R., 1937- (CABI North American Office, 2009)
The extreme climate variability that characterizes China's arid rangelands can cause drought and degradation, resulting in dust storms, floods, animal losses, financial hardship and a decline in food availability. Faced with the possibility of even greate.